Implementasi Kebijakan Desentralisasi Pendidikan di MTS Hifzil Quran Yayasan Islamic Center Medan - Mukhlasin, Ahmad; Azizah, Elvi; Aulia, Putri Febby; Nst, Mhz Irgi Maulana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Maintaining the decentralization of education, the local government as the owner of the highest authority in the region has power in terms of arrangement, management, construction, as well as supervision. That is why the commitment of local governments toining decentralized education is essential. The research methods used are qualitative methods. The data collection techniques used are interviews and observations. Decentralization of education is an environmental process and can lead to significant changes in the policy-making methods of the education system, energy procurement, funding, teacher training, curriculum development and school management. Learning is vital to economic development, and the school system is a tool for strengthening political influence and implementing the programmes and purposes of the rulers. The implementation of decentralization policies is that the implementation process is long and complex, requires adequate resources, and requires good coordination between central and regional governments.